Military Unit in Terytrium Community – Good Neighbour - Sirko, Stanisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article presents selected study directions, which was executed among inhabitants and representatives of local governments in which there are, or were stationed military unit in the past. In carrying out the studies, it was seeking the view of respondents on the impact of the military unit on the socio-economic situation.